Novel Case of Ipsilateral Supracondylar Fracture with Distal Radio-Ulna Fracture with Acute Compartment Syndrome: A Rare Case Report - Sumedh D Chaudhary; Akshay Phupate; Nilesh S Sakharkar; Karan R Lakhani (Journal of Orthopaedic Case Reports)
Introduction: Fractures involving the supracondylar or distal end radius are the most common fracture in pediatric population. Although they have similar mechanisms of injury, i.e., hyperextension, they occur in isolation and combined supracondylar and distal end radius injuries in the same limb are extremely uncommon. We are reporting an extremely rare clinical presentation of a child with ipsilateral supracondylar fracture with fracture of distal end radius and ulna associated with acute compartment syndrome (ACS). Case Report: A 13-year-old male had sustained trauma to left upper limb due to fall from tree. He was initially treated elsewhere with suturing of wound over his forearm and was brought to our emergency room after 12 h with complaints of swelling and severe pain in left arm, forearm, and hand. On clinical examination, there was tense swelling over the left arm, forearm, and hand. Passive stretch pain was present. Limb was warm, there were multiple blisters present over the flexor aspect over anti-cubital fossa of the left limb. On vascular and neurological evaluation, sensation was decreased compared to other limb over the volar aspect of the hand and forearm, also the pulses were feeble. The patient was immediately sent for Doppler of the left upper limb which showed biphasic flow. X-rays revealed ipsilateral left supracondylar humerus fracture (Type 4 according to Gartland Classification) with distal end radius and distal ulna fracture. As the patient had developed ACS which was evident from the tense swelling and passive stretch pain, we decided to urgently operate the patient with fasciotomy followed by fracture fixation. Wound was closed by shoelace suturing technique, and then, split-thickness skin grafting was done. K-wires were after a period of 6 weeks and gradual range of motion exercises was started. Conclusion: Ipsilateral supracondylar with distal end radius with ACS is a rare entity. ACS should be given priority and fasciotomy must be done properly so as to ensure adequate decompression of intercompartmental pressure. This should be followed by fixation of the fractures. If appropriate intervention is done urgently, good results can be achieved even in such challenging injuries.